Female Breadwinners in the Algerian Household: the Paradox of Empowerment - BOUGUESRI , Imene; NAIT-BRAHIM, Abdelghani (Journal of Human Sciences, 2022)
In Algeria, an increasing number of females are facing the reality of being the primary or sole earner in their households in addition to bearing the responsibility of domestic labor that remains static within the family. In the present research work, we hypothesize that women empowerment through access to education and finances may have a positive impact on women’s personal well-being but inflict negative outcomes on their family well-being when they are the primary breadwinner or higher earner. The quantitative findings reveal that women’s psychological well-being is positively impacted by their status given that it guarantees them independence and fulfills their sense of achievement. Whereas the family well-being variable was found to be negatively impacted by their status. We further elucidated women’s interaction patterns within the household through the qualitative findings that report the existence of techniques of governmentality that keep women’s subordination within the household.